Quality of Tourism in World Heritage Sites: A Way towards Sustainability - NAIR, Bipithalal Balakrishnan (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
Quality issues around tourism are indicators for tourism demand, destination development, the visitor’s experience; environmental quality; and community participation. However, the search for quality issues in the tourism industry has been developed further through a one-dimensional approach concentrating specific questions on certain areas of tourism. This study intends to envisage the paradigm of tourism quality as a tool for overall destination development. This research has adopted an interpretive approach to explore multiple viewpoints about the quality of tourism. The findings explore the visitor’s experience, the residents’ perceptions, local issues, and destination management issues associated with the group of monuments in Mahabalipuram. This study enhances tourism literature by offering a framework of quality of tourism, which can be used as a gap analysis tool to identify the core areas of required development. The study also provided implications for management.